Topological momentum skyrmions in Mie scattering fields - Chen Peiyang; Lee Kai Xiang; Meiler Tim Colin; Shen Yijie (Nanophotonics)
How topologies play a role in light–matter interaction is of great interest in control and transfer of topologically-protected structures. These topological structures such as skyrmions and merons have not yet been found in canonical momentum fields, which are fundamental in mechanical transfer between optical and matter fields. Here, we reveal the universality of generating skyrmionic structures in the canonical momentum of light in multipole Mie scattering fields. We demonstrate the distinct topological stability of canonical momentum skyrmions and merons, and compare with well-studied Poynting vector and optical spin fields. The study of these fields allow for a clean and direct approach to measuring and quantifying energetic structures in optical fields, through observable radiation pressure. Our work lays the foundation for exploring new topologically nontrivial phenomena in optical forces, metamaterial design, and light–matter interaction.